The Umayyads' view of the caliphate and their justifications for remaining in power - اسماعیل, سەڵاح کانبی (Sulaimani Journal for Humanities, 2020)
As a result of conflicts between Muslims, The Umayyad Caliphate was born. For instance, the dispute between Umayyad dynasty and Ali ibn Abi Talib. Umayyad family reckoned that caliphate and authority have to pass down power within their family. For this purpose they fell in war and conflict with others including Ali ibn abitalib and some other groups that all of them believe caliphate rights return to themselves. Also, they had different idea about caliphate. This research includes two sections. The first section was dedicated to pledge to Othman calipha, average of Othman blood and sanctification of the caliphate. The second section was dedicated to violence and methods of repression.